PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. JOEY SASMITA LENCANA CABANG PEKANBARU - Dzikra, Faira Medina (Eko dan Bisnis: Riau Economic and Business Review, 2021)
Abstract : Humans are one of the important resources owned by an organization or company. Resources owned by an organization, especially human beings, are an asset that must be maintained and empowered in order to be able to provide maximum contribution to the development and growth of the company. Increasingly complex performance demands. It takes good management in managing existing human resources. In general, the purpose of this study is to determine the effect of supervision on employee work discipline at PT. Joey Sasmita Badge Pekanbaru Branch. The number of samples in this study were 49 people. From the results of the validity test, the whole statement items between the supervisory variable and the work discipline variable were declared valid because the rcount > rtable (0.281) was obtained. The results of simple linear regression obtained the value of Y = 7,296 + 0.720X. From the results of the partial test or t test, it is obtained that the value of tcount (12.833) > from the value of ttable (2.011) with a significant level of 0.000 < 0.05, which means that the monitoring variable has a positive and significant effect on the work discipline variable. And the coefficient of determination R2 of 0.778 means the contribution or magnitude of the influence of supervision on work discipline is 0.778 or 77.8 % while the remaining 22.2 % is influenced by other variables that are ignored or not examined in this study.